2010
DOI: 10.1063/1.3432438
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit interaction effects on magnetoresistance in graphene-based ferromagnetic double junctions

Abstract: Based on the transfer-matrix method, the spin polarized transport properties through a ballistic graphene-based quantum tunneling junctions with the spin-orbit interaction have been investigated. It is found that the magnetoresistance (MR) oscillates with the Rashba spin-orbit interaction (RSOI) and the intrinsic spin-orbit interaction (ISOI). In addition, when the RSOI is present, the negative MR can be observed due to the spin-flip effect, whereas for the ISOI alone no such negative MR can be found. It is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…The undimensional Hamiltonian operator describing pseudospin in single-layer graphene, spin-orbital interaction, electric and magnetic field (the last is normal to graphene layer) has the following matrix form [1][2][3][4][6][7][8] Here (x,y) and (x,y) are coefficients of extrinsic, or Rashba, and intrinsic spin-orbit coupling, respectively [8], M(x,y) is proportional to the coefficient of interaction and magnetization of substrate (which can include an inhomogeneous or periodical ferromagnetic structure); U(x,y) is scalar electrostatic potential describing inhomogeneous bias electric field, A y  A(x,y) is the vectorpotential of the magnetic field. The spin-orbital Rashba interaction appears due to lacking of inversion symmetry, for example due to substrate at one side of the graphene layer.…”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undimensional Hamiltonian operator describing pseudospin in single-layer graphene, spin-orbital interaction, electric and magnetic field (the last is normal to graphene layer) has the following matrix form [1][2][3][4][6][7][8] Here (x,y) and (x,y) are coefficients of extrinsic, or Rashba, and intrinsic spin-orbit coupling, respectively [8], M(x,y) is proportional to the coefficient of interaction and magnetization of substrate (which can include an inhomogeneous or periodical ferromagnetic structure); U(x,y) is scalar electrostatic potential describing inhomogeneous bias electric field, A y  A(x,y) is the vectorpotential of the magnetic field. The spin-orbital Rashba interaction appears due to lacking of inversion symmetry, for example due to substrate at one side of the graphene layer.…”
Section: Basic Equationsmentioning
confidence: 99%
“…|1,2,3,4 | 2 at the resonant value  = 0.748 on the Rashba parameter . Parts b)-e) are the distributions of | 1,2,3,4 | 2 for the value  = 0.015.…”
mentioning
confidence: 99%
“…By utilizing and controlling the spin characteristic of carriers, spin dependent transport through ferromagnetic graphene and graphene-based devices has been widely studied [26,27]. The magnetoresistance of graphene tunnel junctions has been demonstrated at [28][29][30] in the presence of spin-orbit effect and under the combined modulation of strain and Rashba SOI at [9]. Graphene-based spin diode and spin transistors have been studied at [9,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…43 In a recent study, Fallah and Esmaeilzadeh have shown that, in the presence of proper Rashba spin-orbit strength, an organic (1,4-2phenyl-dithiolate) molecule can act as an electron spin inverter. 44 Although spin-dependent electron transport in graphene has been studied extensively in recent years, [21][22][23][24][25][26][27][28] to the best of our knowledge, electron spin inversion in graphene has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-dependent electron transport in graphene has been studied vastly in recent years (see e.g., Refs. [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%